PERSPEKTIF ADMINISTRASI PEMBANGUNAN: MENUJU KE ARAH KONVERGENTIF - Engkus, Engkus (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
Researchers now indicate that development administration in the context of social change argues that it is evolving progressively from backwardness, dependence and modernization. That theoretically teaches the third world specifically in the perspective of classical theory, and contemporary perspectives. Classically it seems, in its development the development perspective is towards convergence, because there tends to be some similarity in elements. There is an effort to bring back historical analysis. With the method of historical assessment, social reality is always continuously in the process of change. Unlike dependency theory which focuses on the heyday and bankruptcy of a country, the world system perspective studies the dynamics of the history of the world economic system. Furthermore, the development perspective seems to try to test problems that have been formulated using variables simultaneously, statements about the positive or negative consequences of development remain left open.